Informative function of law and its influence on legal culture of a society - Макеєва, Олена Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
Informative society is a society of advanced information production and the high legal of culture. Investigation of the informative function of law will allow to analyze the problem of legal culture at the present stage of development of Ukraine, legal education of the population and officials. The aim of the article is to study the concept of the informative function of law, its implementation mechanism and influence on the formation of legal culture of a society. Functions of law are the main directions of its influence on behavior of subjects of public relations due to its essence and social purpose. Informative function of law exists to give the legal information to the citizens, influences of legal consciousness of an individual and on the formation of legal culture of a society. The mechanism of realization of the informative function of law is the system of legal information, subjects, objects and legal means of legal information that help to maintain information integrity of the legal system. Implementation of the informative function of law embodied in providing the access of citizens and officials to legal information, it appears in the following forms: informative-psychological, educational and social. In modern conditions the concept of formation of legal culture of a society should be the important part of the state information policy, the necessary basic component of which is legal knowledge id est sufficient knowledge of public officers and citizens about the rights, duties that are provided for by legal norms. Further scientific investigation of the problems of the informative function of law and its impact on social legal culture is necessary for the rule of law, effective law-making and law enforcement activities, to ensure law and order in a society. The level of legal culture of a society depends on effectiveness of the informative influence of law.